Conflict then; trauma now: Reading Vietnam across the decades in American comics. Issue 2 (1st June 2018) - Earle, Harriet
This article will consider the shift in representations of the Vietnam War in American comics, concentrating specifically on the shift from gung-ho violence and patriotism to nuanced personal narratives of trauma and the psychological impact of conflict. I will compare and contrast three comics series: The 'Nam, a Marvel series that ran from 1986 to 1993; The Punisher Invades the 'Nam, a cross-over series that comprises two arcs over five issues in 1990 and 1992; and Garth Ennis and Darick Robertson's The Punisher: Born ([2003] 2007), an origin story that positions trauma as a survival tool within theatre. Vietnam as a conflict event and a cultural touchstone has affected the way we view violence in the twenty-first century. I discuss how comics has measured and represented the shift in positioning of violence and conflict from earlier wars through Vietnam to the present day. I close by asking to what extent our tools and tropes for representation of violence have changed and ask if there remain some last strands of continuity from pre-Vietnam violence texts.